A Survival Analysis of Student Mobility and Retention in Indiana Charter Schools - Holmes Finch; Dan Lapsley; Mary Baker-Boudissa (Arizona State University, 2009)
﻿Research has demonstrated that high rates of student mobility are associated with a range of negative academic outcomes, both for students who leave their schools and those who remain behind. The current study focused on mobility among those enrolled in charter schools in the state of Indiana. A multilevel Cox Proportional Hazards survival analysis model was used to identify significant predictors of student mobility within and from a state charter school system, using factors at both the student and school levels. Results indicated that initial student achievement upon first entering a charter school, student ethnicity, participation in a Title I funded program, and average years of teacher experience at the school were all associated with the decision to leave the charter. Specifically, students with higher initial achievement scores, those eligible for Title 1 services, and non-Caucasian students were more likely to leave charter schools prematurely. In addition, schools with a more experienced faculty had lower early departure rates than did those with less experienced teachers.